MIKROTEXTE AUF (DE)MOTIVIERENDEN SEHFLÄCHEN - Makowska, Magdalena (Acta Neophilologica, 2013)
The article constitutes an attempt to answer the question whether demotivators being popular in multimedia communication can be treated as an example of verbal – iconic texts which have a right to an visual planes status. In the present article an answer is sought to the question in what semantic relation the elements of the verbal and iconic layer of a given demotivator remain with regard to each other as well as what function can be ascribed to them. In reference to the theory of microtexts according to Hardarik Blühdorn presented is also the author’s own concept of microtext which integrates verbal and iconic elements. A formal, semantic and functional analysis of demotivators serves to demonstrate that they are entitled to the status of visual planes.